2020
DOI: 10.14283/jpad.2020.32
|View full text |Cite
|
Sign up to set email alerts
|

Toulouse Alzheimer’s Clinical Research Center Recovery After the Covid-19 Crisis: Telemedicine an Innovative Solution for Clinical Research During the Coronavirus Pandemic

Abstract: In the context of the COVID-19 pandemic (1)(2) declared by the World Health Organization in March 2020, the French government decided to lockdown the entire country on March 17th. Consequently, the ongoing recruitment of participants for the INSPIRE study (3, 4) was temporarily interrupted on March 16th and the 123 future participants programmed until April 30th were postponed (5). In France, only emergencies were allowed to be physically seen. As an alternative for the other patients, Telemedicine has become … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 8 publications
2
9
0
Order By: Relevance
“…Remote assessments may provide a useful means of testing large numbers of study participants for longitudinal, observational studies as well as for screening for inclusion and follow-up in large-scale prevention/intervention trials, 8 with high acceptance rate in seniors (90% in our study; 88.6% in Takeda et al 8 ). A pilot study on remote assessment revealed that once older adults had coped with a first remote assessment in digital format the dropout was minimal.…”
Section: Implications For Wider Research and Future Considerationsmentioning
confidence: 74%
“…Remote assessments may provide a useful means of testing large numbers of study participants for longitudinal, observational studies as well as for screening for inclusion and follow-up in large-scale prevention/intervention trials, 8 with high acceptance rate in seniors (90% in our study; 88.6% in Takeda et al 8 ). A pilot study on remote assessment revealed that once older adults had coped with a first remote assessment in digital format the dropout was minimal.…”
Section: Implications For Wider Research and Future Considerationsmentioning
confidence: 74%
“…We cannot afford to discontinue these trials, nor to threaten the validity of the evidence they provide in these situations [ 18 ]. Our group, like others, has been able to come up with ad-hoc plans to cope with the situation and maintain clinical research [ 19 ], but not without great burden. Although the overall results of these ad-hoc plans have been positive, we should not have to rely on this type of site-based initiatives.…”
Section: Discussionmentioning
confidence: 99%
“…Virtual visits could also be used for trial components that do not require technically invasive procedures. The INSPIRE study team at Toulouse University Hospital tested this strategy following the first COVID lockdown in France and found a high rate of acceptance among participants ( 33 ).…”
Section: Moving Forwardmentioning
confidence: 99%